Perbedaan Percepatan Pertumbuhan Anak Stunting Berdasarkan Kelompok Umur Yang Mendapat Intervensi MP-ASI Berbasis Ikan Tuna - Setha, Beni; Loppies, Cindy R M; Savitri, Imelda K E; Pagaya, Joseph; Lapu, Petrus; Tahitu, Ritha; Kusadhiani, Indrawanti (Universitas Pattimura, 2024)
Tuna (Thunnus sp.) is a rich source of animal protein, containing high levels of protein and omega-3 fatty acids, particularly EPA and DHA, and has fine meat fiber. Therefore, tuna fish is an excellent source of animal protein for producing complementary foods to meet the protein needs of breastfed infants and children under five. This study aims to assess the differences in average height and weight of children according to age before and after receiving fish-based and processed complementary foods. The research involved 25 stunted children aged 6-36 months, who were given. Fish-based complementary food and processed fish complementary food (meatballs and nuggets) twice a day for 36 days. Data on children's height and weight were collected before and after the intervention. A paired t-test with a significance level of 95% (alpha 0.05) was used to analyze the data. The results showed a significant difference in children's average height and weight before and after the intervention of fish-based and processed complementary foods. On average, the children's height increased by 3.22 cm, and their weight increased by 1.12 kg after receiving the fish-based complementary foods.